Rare case of EBV-induced colitis in an immunocompetent individual - Catherine Choi; Qi Yu; Pratik Q Deb; Weizheng Wang (BMJ Open Gastroenterology, 2020)
Epstein-Barr virus (EBV) is a member of the herpes virus family and affects people worldwide. EBV-infected colitis can occur in patients in immunocompromised states. However, EBV-induced colitis in immunocompetent patients is extremely rare. A 34-year-old man with a prior history of possible intussusception, and who underwent a right hemicolectomy, presented with abdominal pain and rectal bleeding. Laboratory investigations were unremarkable, and the patient underwent a colonoscopy, which showed EBV-infected colitis. Both infectious and inflammatory bowel disease (IBD) workups were negative. The patient’s symptoms were resolved with supportive therapy. A repeat colonoscopy showed normal colonic mucosa with an absence of EBV infection. Without evidence of IBD or infectious aetiologies, EBV-associated colitis is a rare finding in an immunocompetent patient.